Toward understanding the contribution of waterbodies to the methane emissions of a permafrost landscape on a regional scale: a case study from the Mackenzie Delta, Canada - Kohnert, Katrin; Antonova, Sofia (Global change biology, 2018)
Waterbodies in the arctic permafrost zone are considered a major source of the greenhouse gas methane (CH4) in addition to CH4 emissions from arctic wetlands. However, the spatio-temporal variability of CH4 fluxes from waterbodies complicates spatial extrapolation of CH4 measurements from single waterbodies. Therefore, their contribution to the CH4 budget of the arctic permafrost zone is not yet well understood. Using the example of two study areas of 1,000 km² each in the Mackenzie Delta, Canada, we approach this issue (i) by analyzing correlations on the landscape scale between numerous waterbodies and CH4 fluxes and (ii) by analyzing the influence of the spatial resolution of CH4 flux data on the detected relationships.